Protecting stateless children in South Africa through nationality: a children's rights approach - Maziya, Nokwanda Takalanga (Rhodes University, Faculty of Law, Law)
This study investigates the role of nationality in protecting stateless children. Under interna-tional human rights law, all individuals, including stateless persons, are entitled to certain rights by virtue of being human. Consequently, stateless children should theoretically have access to fundamental rights such as education, healthcare, and social security, even without nationality. However, this study challenges the assumption that stateless children can access these rights merely because they are human. The study reveals that, in practice, stateless chil-dren struggle to access essential rights like education, healthcare, and social welfare without nationality. The study asserts that nationality is crucial for stateless children to access basic rights in South Africa. The study examines various treaties related to nationality and con-cludes that none impose a binding obligation on South Africa to confer nationality on state-less children. The study then draws on international children's rights principles such as the best interest of the child, the right to life, survival and development, and the right to non-discrimination to demonstrate that despite a clear obligation on South Africa in terms of trea-ty law to grant nationality to stateless, these principles, place limits on South Africa's exer-cise of sovereign power. This, in turn, makes way for granting nationality to stateless chil-dren.
Keywords: Citizenship; Stateless persons; Children's rights; Human rights; Sovereignty